Turkish university students' attitudes toward rape - Gölge, ZB; Yavuz, MF; Müderrisoglu, S; Yavuz, MS (Kluwer Academic/Plenum Publ, 2003)
In this study we investigated the effects of gender and gender roles upon attitudes toward rape among 432 female and 368 male college students in Turkey whose mean age was 22.08 (SD = 2.09). The Bem Sex Role Inventory (BSRI) and measures of attributions toward date rape and stranger rape, and myths scenarios were used. All 3 scenarios were given to each participant. It was hypothesized that women would attribute less responsibility than men would to the rape victim, more responsibility to the assailant, and describe the assault as a serious crime. Women and men who have masculine gender roles were expected to attribute more responsibility to the rape victim and less responsibility to the assailant and show higher tolerance of the assault than would those in the other classified gender roles. Both men and women were expected to attribute more responsibility to the victim of a date rape and less responsibility to the date rape assailant and show higher tolerance of date rape than stranger rape. Results indicated that gender, but not gender role, was an important factor in Turkish college students' attitudes toward date rape. Women and men shared a similar point of view on stranger rape, but date rape was considered less serious than stranger rape. Gender role was not a significant factor in attitudes toward rape.
Keywords: Rape; Gender; Gender Role; Sexual Assault; Date Rape; College-Students; Victims; Aggression; Women; Myths